West Nile virus in California, 2003–2018: A persistent threat - Snyder, Robert E.; Feiszli, Tina; Foss, Leslie; Messenger, Sharon; Fang, Ying; Barker, Christopher M.; Reisen, William K.; Vugia, Duc J.; Padgett, Kerry A.; Kramer, Vicki L. (PLOS Neglected Tropical Diseases, 2020)
Author summary West Nile virus (WNV) was first detected in the United States in 1999, and subsequently spread throughout the country. It is now the most commonly reported disease that is transmitted by mosquitoes in the United States. California has reported approximately 15% of all human WNV infections since the virus was first reported in the state in 2003. The California Department of Public Health works with partners throughout the state to conduct robust surveillance of WNV infections in mosquitoes, dead birds, and sentinel chickens, using these data to direct vector control activity and reduce the risk of WNV transmission to people. This article summarizes sixteen years of human, mosquito, chicken, equine, and dead wild bird surveillance for WNV in California, the most comprehensive description of WNV surveillance data to date. We found that WNV enzootic and human activity varied geographically and in intensity from year-to-year. Almost 95% of all WNV activity in California occurred in the Central Valley and southern California between April and November.